Ochrona uchodźców w ustawodawstwie państw członkowskich Unii Europejskiej z Europy środkowej i wschodniej - Potyrała, Anna (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The paper aims to analyze the asylum policies of new EU member states from Central and Eastern Europe. After The Hague Program Strengthening Freedom, Security and Justice in the European Union was announced in 2004 the refugee policies of various countries were to be harmonized and a Joint European Asylum System was to be established on the basis of legal and institutional foundations. The initiatives focused on the adoption of common solutions concerning asylum procedures, the conditions for admitting individuals applying to be considered refugees in the EU, temporary and subsidiary protection, and the criteria for granting asylum. As negotiations with candidate countries commenced, they needed to adapt their national laws to the requirements of European legislature. Candidate countries initiated changes in their national legal systems. However, some solutions they have introduced defy the international obligations following from the 1951 Convention relating to the Status of Refugees and recommendations of the UN High Commissioner for Refugees. Particular controversies concern the concept of safe states, where refugees are deprived of the possibility of applying for the protection of the EU, as well as the concept of subsidiary and temporary protection allowing for individual applications for asylum not to be considered.
Protection of refugees in the legislature of European Union member states from Central and Eastern Europe
Keywords: uchodźstwo; Unia Europejska; ustawodawstwo; Europa Środkowo - Wschodnia